Photo-excitable hybrid nanocomposites for image-guided photo/TRAIL synergistic cancer therapy. (September 2018) - Lin, Gan; Zhang, Yang; Zhu, Congqing; Chu, Chengchao; Shi, Yesi; Pang, Xin; Ren, En; Wu, Yayun; Mi, Peng; Xia, Haiping; Chen, Xiaoyuan; Liu, Gang
Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) can induce apoptosis in cancer cells without toxicity to normal cells. However, the efficiency is greatly limited by its short half-life and wild resistance in various cancer cells. In this study, we reported a micellar hybrid nanoparticle to carry TRAIL ligand (denoted as IPN@TRAIL) for a novel photo-excited TRAIL therapy. These IPN@TRAIL offered increased TRAIL stability, prolonged half-life and enhanced tumor accumulation, monitored by dual mode imaging. Furthermore, IPN@TRAIL nanocomposites enhanced wrapped TRAIL therapeutic efficiency greatly towards resistant cancer cells by TRAIL nanovectorization. More importantly, when upon external laser, these nanocomposites not only triggered tumor photothermal therapy (PTT), but also upregulated the expression of death receptors (DR4 and DR5), resulting in a greater apoptosis mediated by co-delivered TRAIL ligand. Such photo/TRAIL synergistic effect showed its great killing effects in a controllable manner on TRAIL-resistant A549 tumor model bearing mice. Finally, these nanocomposites exhibited rapid clearance without obvious systemic toxicity. All these features rendered our nanocomposites a promising theranostic platform in cancer therapy.